Pengaruh Stimulasi Perkembangan Anak Oleh Guru Paud Terhadap Perkembangan Anak Paud Di Paud Gugus IX Kel. Pandanwangi Kota Malang - Ngesti w Utami; Anggi Ardhiasti (Jurnal Pendidikan Kesehatan, 2020)
Child development happens at the golden age when children are at the age of 24 until 36 months. At this age, stimulation treatment will be more effective, as has been done in PAUD or Early Childhood Education. The purpose of this study was to determine the effect of developmental stimulation given by teacher to paud students of the age group 24 until 36 months. The teacher who will provide developmental stimulation to the students of the paud child, has previously been given education and skills training related to developmental stimulation for the students. The Quasy experimental research method is used by providing stimulation treatment to a group of students aged 24 until 36 totaling 30 children, and choosing 30 aged 24 until 36 months as a control group without being given developmental stimulation. The sample selected in this study was 60 students of PAUD from PAUD cluster IX, Pandanwangi Urban Village. The results showed that 68 percent of the group specifically stimulated by the teacher were in normal development, and 72 percent in the group without special stimulation were in normal development. Both of them did not show any significant difference, with a value of 0.833, which was greater than 0.05, so H1 was rejected. There are many factors that can affect a child development at the age of 24 until 36 months. Either external and internal environmental of each child play a role. Paud as the education centre and its facilities are also factors that contribute to the development of early childhood students of cluster IX in Pandanwangi Village, Blimbing District, Malang City. For this reason, the existence of Paud as a place for children from the age of 24 months to participate in learning and playing activity becomes effective as a media for stimulating the development as well. Therefore, parents and teachers in paud are suggested to provide stimulation for children according to the material guidelines in KPSP that are trusted and easy to do